English Language Teachers' Knowledge, Use, and Perceived Effectiveness of Action Research for Professional Development - Rauteda, Khem Raj (Indonesian Journal of English Language Studies (IJELS), 2025)
In light of evolving pedagogical frameworks and increasing challenges in English Language Teaching (ELT), effective professional development is essential for teachers striving to enhance their practices. Action research is a pivotal strategy for teachers' professional development, fostering an adaptive learning environment through reflective pedagogy. While teachers have implemented action research, its engagement among secondary-level English language teachers remains underexplored, particularly regarding their knowledge, use, and perceptions of its role in professional growth. The study aimed to identify secondary-level English language teachers’ knowledge, use, and perceived effectiveness of action research as a tool for professional development. The research employed a quantitative survey approach, focusing on English language teachers in private and public schools in Nepal, with a particular emphasis on those in the Sunsari district. A sample of 200 teachers was selected using a simple random sampling strategy, and a structured questionnaire was administered online via Google Forms. The collected data were analyzed using a bivariate analysis approach with SPSS. A chi-square test was conducted to assess the association between the variables, while Phi was employed to determine the significance of these relationships. The study examined the association between independent variables (such as sex, level of teaching, type of school, and academic qualification) and dependent variables (including use of action research, knowledge of action research, and perceived effectiveness of action research). The findings indicated no significant statistical association between the independent and dependent variables. However, the study concluded that the majority of teachers perceived action research as valuable for problem-solving, increasing professional confidence, promoting career advancement, fostering transformative agency, and enhancing teacher collaboration. It suggests that teachers could benefit from more effectively integrating action research into their teaching practices for professional development and transformation.